Pengaruh Servant Leadership Dan Budaya Kerja Terhadap Kinerja Karyawan El Zatta Hijab - Husein Kuncoro Jati; Sri Suwarsi (Bandung Conference Series: Business and Management, 2022)
Abstract. This research is entitled “The Influence of Servant Leadership and Work Culture on El Zatta Hijab Employee Performance. This study aims to prove that there is a positive and significant effect of Servant Leadership and Work Culture on the performance of El Zatta Hijab employees. Partially and simultaneously. Population 150. A sample of 110 was determined based on the Taro Yamane formula. The result of this research is the Multiple Linear Regression Equation Y = a + b1X1 + b2X2 . Y = Y=2,369 + 0.687 X1 + 0.431 X2 The meaning of this Multiple Linear Regression Equation is Without Servant Leadership and Work Culture, then the value of Employee Performance is only 2,369. Employees who were originally only 2,369, will increase to 2,369 + 0.687 + 0.431 to 3,487. F value count 219,741. The value of F Table is 3.93. So F Count > F Table. Paying attention to F Count > F The author's table can prove that there is a positive influence of Servant Leadership and Work Culture on Employee Performance simultaneously. The t value of calculating the influence of Servant Leadership on Employee Performance is 7,810. It means t count > t table. Paying attention to the value of t arithmetic > t table and it can be said that there is a positive influence of Servant Leadership on Employee Performance. The t value of the influence of Work Culture on Employee Performance is 6.947. It means t count > t table. Taking into account the value of t count > t table, it can be said that there is a positive influence of Work Culture on Employee Performance. If you want to improve employee performance, the first thing that must be improved is work culture, then the implementation of Servant Leadership, then improved employee performance. Abstrak. Penelitian ini berjudul “Pengaruh Servant Leadership dan Budaya Kerja Terhadap Kinerja Karyawan El Zatta Hijab. Penelitian ini mempunyai tujuan untuk membuktikan terdapat pengaruh positif dan signifikan Servant Leadership dan Budaya Kerja terhadap kinerja karyawan El Zatta Hijab secara parsial dan secara simultan. Populasi 150. Sampel sebanyak 110 ditetapkan berdasarkan rumus Taro Yamane. Hasil penelitian berupa Persamaan Regresi Linier Berganda Y = a + b1X1 + b2X2 . Y = Y=2,369 + 0,687 X1 + 0,431 X2. Makna dari Persamaan Regresi Linier Berganda ini adalah Tanpa Servant Leadership dan Budaya Kerja, maka nilai Kinerja Karyawan hanya sebesar 2,369. Tetapi jika dilakukan penambahan Servant Leadership dan Budaya Kerja dan penambahan dilakukan secara simultan maka nilai Kinerja Karyawan yang semula hanya 2,369, maka akan berubah meningkat menjadi 2,369 + 0,687 + 0,431 menjadi 3,487. nilai F hitung 219,741. Nilai F Tabel sebesar 3,93. Jadi F Hitung >F Tabel. Memperhatikan F Hitung > F Tabel penulis dapat membuktikan bahwa terdapat pengaruh positif Servant Leadership dan Budaya Kerja Terhadap Kinerja Karyawan secara simultan. Nilai t hitung pengaruh Servant Leadership terhadap Kinerja Karyawan sebesar 7,810. Artinya t hitung > t tabel. Memperhatikan nilai t hitung > t tabel dan dapat dikatakan bahwa terdapat pengaruh positif Servant Leadership terhadap Kinerja Karyawan. Nilai t hitung pengaruh Budaya Kerja terhadap Kinerja Karyawan sebesar 6,947. Artinya t hitung > t tabel. Memperhatikan nilai t hitung > t tabel dapat dikatakan bahwa terdapat pengaruh positif Budaya Kerja terhadap Kinerja Karyawan. Jika ingin memperbaiki kinerja karyawan yang harus diperbaiki lebih dahulu adalah budaya kerja, selanjutnya pelaksanaan Servant Leadership, kemudian kinerja karyawannya yang diperbaiki.